Visual design solutions : principles and creative inspiration for learning professionals - Malamed, Connie (Hoboken, New Jersey : John Wiley & Sons, 2015)
Enhance learners' interest and understanding with visual design for instructional and information products No matter what medium you use to deliver content, if the visual design fails, the experience falls flat. Meaningful graphics and a compelling visual design supercharge instruction, training, and presentations, but this isn't easy to accomplish. Now you can conquer your design fears and knowledge gaps with Visual Design Solutions: a resource for learning professionals seeking to raise the bar on their graphics and visual design skills. This informal and friendly book guides you through the process and principles used by professional graphic designers. It also presents creative solutions and examples that you can start using right away. Anyone who envisions, designs, or creates instructional or informational graphics will benefit from the design strategies laid out in this comprehensive resource. Written by Connie Malamed, an art educator and instructional designer, this book will help you tap into your creativity, design with intention, and produce polished work. Whereas most graphic design books focus on logos, packaging, and brochures, Visual Design Solutions focuses on eLearning, presentations, and performance support. Visual Design Solutions includes practical guidelines for making smart design choices, ways to create professional-looking products, and principles for successful graphics that facilitate learning. Ideal for instructional designers, trainers, presenters, and professors who want to advance from haphazard to intentional design, this book will help them realize their design potential. Gain the knowledge and confidence to design impressive, effective visuals for learning Increase learner comprehension and retention with visual strategies offered by an expert author Serves as a reference and a resource, with a wealth of examples for inspiration and ideas Addresses an intimidating topic in an informal, friendly style In four parts, the book provides a thorough overview of the design process and design concepts; explores space, image, and typography; and presents workable solutions for your most persistent and puzzling design problems. Get started and begin creating captivating graphics for your learners.
Part 1, The big ideas: Like a hand in glove -- Think like a designer ; you are one -- Work like a designer -- Part 2, Building blocks of design: Organizing graphic space -- Selecting and creating images -- Working with type -- Part 3, Power principles: Use color with purpose -- Establish a visual hierarchy -- Unify the design -- Create contrast -- Group for meaning -- Part 4, Practicing design: Show them where to look -- Add some excitement -- Enhance meaning -- Tell stories with visuals -- Make numbers interesting.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
English.
John Wiley and Sons
Keywords: Visual sociology; Visual communication; Commercial art; Sociologie visuelle; Communication visuelle; Art publicitaire; commercial art; BUSINESS & ECONOMICS -- Training; Commercial art; Visual communication; Visual sociology